تكييف مسؤولية الرياضي والمدرب الناجمة عن تعاطي المنشطات في القاعات الرياضية: كمال الأجسام أنموذجا: دراسة تحليلية مقارنة - أحمد، شنه شريف; سمايل، تحسين حمد (جامعة البصرة - مركز دراسات البصرة والخليج العربي, 2022)
تعد قضية تعاطي المنشطات المحظورة من أهم المواضيع الحساسة في العصر الحالي، خاصة في مجال (رياضة كمال الأجسام) فإن تعاطي المنشطات المحظورة شائع جدا سواء في مرحلة التدريب في قاعات اللياقة البدنية أو عند المشاركة في المسابقات والألعاب الأولمبية وغيرها من المسابقات، والتي تعتمد على استخدام المنشطات الرياضية لزيادة كفاءة الرياضيين والفوز في المنافسات، وغالبا تتم استخدامها من قبل الرياضيين بصورة غير قانونية بعيدا عن المجال الطبي، وبدون استشارة الأخصائيين والأطباء، لأنه في العراق لا يوجد قانون خاص يناهض ويكافح استخدام المنشطات مما أضر كثيرا بالرياضيين. تناقش هذه الدراسة بيان طبيعة المسؤولية المدنية للمدرب والرياضي عند استخدام المنشطات الرياضية الخطرة والمحظورة بشكل غير قانوني وخارج نطاق الرعاية الطبية، والأصل أن مسؤولية المدرب هي مسؤولية عقدية، حتى وإن لم يكن هناك رابطة عقدية مباشرة بين الرياضي المتضرر والمدرب المسؤول عن الضرر، وتكون مسؤوليته تقصيرية استثناء وفي حالات أخرى، وتناقش هذه الدراسة أيضا الحالات التي يكون الرياضي نفسه مسؤولا عن أضراره بسبب تعاطي المنشطات الرياضية المحظورة، وهذا ما يسبب تخفيف مسؤولية المدرب في الاشتراك في إحداث الضرر أو توزيع المسؤولية، عند حالة الإهمال المشترك أو قبول المخاطر الرياضية. The issue of the abuse of prohibited steroids is one of the most sensitive topics in the current era. Especially in the field of (sports bodybuilding). This sort of abuse is very common, whether it happens during the training phase in fitness halls or when participating in various competitions and Olympic Games due to the fact that they depend on the use of Sports steroids to increase the efficiency of athletes and win competitions. These drugs are frequently used by athletes illegally away from the medical field on different occasions without consulting specialists. The frequent usage goes back to the reason that in Iraq there is no special law that opposes and struggles against the use of steroids, which has greatly harmed athletes. This study discusses the nature of the civil liability of the coach and the athlete when using dangerous sports drugs illegally and outside the scope of medical care. They belong to contractual liability that together represent a contractual group. The coach’s liability is tortuous as an exception in other cases. This study also discusses cases in which the athlete himself is responsible for the damage due to the use of prohibited sports stimulants, and this is what causes the coach’s responsibility to be reduced from participating in the harm events and in the case of joint negligence and acceptance of sports risks.
Keywords: المنشطات الرياضية -- المسؤولية المدنية -- القانون الرياضي -- الألعاب الرياضية -- الصالات الرياضية